Stability improved of improved low energy adaptive clustering hierarchy routing protocol for wireless sensor network - Sabah Talib, Al-Zubaidi Ammar (2017)
Wireless Sensor networks (WSN) consist of a large number of homogeneous or heterogeneous sensor nodes. These nodes are equipped with limited battery capacity and connected wirelessly. They are deployed at various geographical locations to provide the functions of monitoring and tracking of physical events. Gathering sensed data from real world for long period of time in an energy efficient manner is a typical operation in many applications of WSNs. Low Energy Adaptive Clustering Hierarchy (LEACH) is one of the prominent WSN protocol which is developed to prolong the network lifetime by utilizing energy efficient clustering technique. However, there are many limitation in LEACH. An Improved LEACH is one of LEACH variant that was able to reduce power consumption and prolong the overall network life time at the expense of reduced stability period (the time span before the death of first node). Nevertheless, the network stability period is important for many applications that require reliable feedback from the network. Hence, it is motivated us to enhance Improved LEACH algorithm to provide higher stability. In this project, a protocol named Stable Improved LEACH is designed to overcome the shortcomings of Improved LEACH. It balances the load among nodes by utilizing node residual energy and its distance to Base Station in the process of cluster head selection and utilizing node distance to Base Station during the process of Cluster formation. The simulation results revealed that our proposed protocol significantly outperforms Improved LEACH in terms of stability period and network life time.